2003
DOI: 10.1021/ma034350s
|View full text |Cite
|
Sign up to set email alerts
|

Polyisobutylene Stars and Polyisobutylene-block-Poly(tert-Butyl Methacrylate) Block Copolymers by Site Transformation of Thiophene End-Capped Polyisobutylene Chain Ends

Abstract: A new synthetic route for the synthesis of polyisobutylene (PIB) stars and PIB-poly-(methacrylate) block copolymers was developed by combining living carbocationic and anionic polymerizations. Rapid and quantitative monoaddition of thiophene to living PIB chains has been observed in conjunction with TiCl 4 as Lewis acid in n-hexane/CH2Cl2 60/40 v/v at -78 °C leading to the formation of 2-polyisobutylenyl-thiophene (PIB-T). PIB-T was quantitatively metalated with n-butyllithium in THF at -40 °C. 1 H NMR spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 27 publications
(45 reference statements)
1
47
0
Order By: Relevance
“…Thiophene has been found to be a suitable capping agent, which is more successful compared to furan (known to lead to unwanted secondary reactions). 159 Reaction of thiophene-terminated PIB with n-BuLi provides an efficient macroinitiator for anionic polymerization of tBMA. The polyisobutylene hydrophobic block is usually synthesized by a cationic procedure using BCl 3 /TiCl 4 catalyst.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Thiophene has been found to be a suitable capping agent, which is more successful compared to furan (known to lead to unwanted secondary reactions). 159 Reaction of thiophene-terminated PIB with n-BuLi provides an efficient macroinitiator for anionic polymerization of tBMA. The polyisobutylene hydrophobic block is usually synthesized by a cationic procedure using BCl 3 /TiCl 4 catalyst.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…For instance, Müller et al reported the synthesis of PIB-b-poly( t butyl methacrylate) (P t BMA) and poly(methyl methacrylate) (PMMA)-b-PIB-b-PMMA by metalation of DPE end-capped PIB with Na/K alloy or cesium followed by anionic polymerization (3,4). Another attempt demonstrated by Müller et al involved the preparation of thiophene end-functionalized PIB and subsequent metalation of the polymer chain end with an alkyllithium compound, followed by polymerization of t BMA with the generated macroanion (5). In a recent publication, we also reported the synthesis of PIB-b-PMMA by a novel coupling approach combining living cationic and anionic polymerization techniques (6).…”
Section: Introductionmentioning
confidence: 99%
“…The same THF/methanol 80.5/19.5 (w/w) composition has already been employed by Mueller and coworkers for the LCCC analysis of PIB block copolymers. [26] However, this solvent composition is not suitable for high MW PIB as suggested by the very low sample recovery observed with M n = 20900 due to precipitation of the polymer.…”
Section: Lccc Experiments: Determination Of Critical Conditions Of Admentioning
confidence: 99%